Effectiveness of Sammathithi Development Program on Stress Level among Nursing Students - Tantranont, Kunlayanee; Supavititpatana, Bungorn; Sriarporn, Punpilai; Ragsakun, Nisachon; Suankaew, Sukritta (Journal of The Royal Thai Army Nurses, 2022)
Two-group quasi-experimental research with a pretest and a posttest. Objective of this study was to study the effectiveness of Sammathithi development program on stress level among nursing student. 57 third-year nursing students were recruited according to the inclusion criteria and divided into an experimental group (29 students) and control group (28 students). The experimental group received the Sammathithi development program. The data collecting instrument was Suanprung Stress Test-20. The Cronbach’s Alpha Coefficient of the instrument was .91. Repeated measure ANOVA were employed for data analysis. The experimental group’s mean scores of stress level after intervention were decreased significantly (F = 14.24, p<.001). The mean scores of stress level among the experimental group was lower than the control group at 5 weeks and 13 weeks significantly (t = 4.47, p <.001 and t = 4.70, p <.001, respectively). The results revealed that the experimental group receiving the Sammathithi development program could decrease stress level. The program should be applied in order to decrease stress among nursing students.